The Peso Appreciation and the Sustainability of Philippine Growth Need We Worry?. - Fabella, R. V.
The rapid appreciation of the Philippine peso and the resulting loss of competitiveness militate against long-term Òbalanced and sustainable growthÓ. A review of history shows that fighting inflation with appreciation of currency ÒseedsÓ a financial storm. In contrast, the undervaluation of the domestic currency has been shown to robustly improve economic growth in less developed countries like the Philippines. The government, however, need not embark on an aggressive depreciation of the peso but rather on keeping the exchange rate between Php 42 and Php 43 to a dollar for the next five years. This will likely raise further the foreign exchange reserves now at record levels. In order to achieve sustainable growth, the government has to craft an Òexit strategy Òfrom the remittance-driven economy by deploying the remitted OFW money to build first-class infrastructure. This can be done by selling infrastructure bonds to the Bangko Sentral ng Pilipinas, which create further demand for dollars and ease the pressure for appreciation coming from the continuing forex inflows.